The role of the Weberian Reform in European Rubus research and the taxonomy of locally distributed species – which species should we describe?. (27th April 2012) - Haveman, Rense; Ronde, Iris de
<x xml:space="preserve">Abstract</x> After Sudre published his treatment of European Rubi in the early 20th century, Rubus taxonomy in Europe suffered from a scholastic phase and a longer period of stagnation. The so‐called 'Weberian Reform' initiated the necessary revival of European batology. It rests on four major pillars: 1) mapping projects over larger areas, 2) evaluation of type material, 3) visits to loci classici, and 4) evaluation of the status of species by means of their distribution areas. Subsequently, it has become widely accepted in European batology that only species with a distribution area over 50 km should be described. Although this pragmatic species concept has been useful in making a continent‐wide overview of brambles, we argue that it is lacking a scientific basis, and should thus be rejected. There are at least four distinctive problems when treating locally distributed brambles: 1) primary hybrids, 2) locally distributed stabilised apomicts, 3) intraspecific variation in species with a larger distribution range, and 4) unstabilised swarms of hybridogenic biotypes and the derivates thereof (mainly in the montane regions). When facing the problems in Rubus systematics, we argue that all independently evolving lineages should be described as species, including apomictic lineages with very small distribution ranges, both from the mountain‐dwelling glandular series and from the lowlands. Neither primary hybrids (which are not stabilised by apomixis), nor biotypes without an independent and coherent distribution area are independently evolving lineages, and should thus not be described as species. We advocate a restrained attitude when describing new species with limited distribution areas.